Identification of a novel AU-rich-element-binding protein which is related to AUF1 - Dean, J; Sully, G; Wait, R; Rawlinson, L; Clark, A; Saklatvala, J (2002)
The AU-rich element (ARE) is an important instability determinant for a large number of early-response-gene mRNAs. AREs also mediate the stabilization of certain pro-inflammatory mRNAs, such as tumour necrosis factor (TNF)-α and cyclooxygenase-2 (COX-2), in response to inflammatory stimuli. To understand how AREs control mRNA stability, it is necessary to identify trans-acting factors. We have purified a new ARE-binding protein and identified it as CArG box-binding factor-A (CBF-A). The amino acid sequence of CBF-A is highly similar to that of the ARE-binding protein AUF1. Recombinant CBF-A bound the COX-2 and TNF-α AREs, but not a non-specific control RNA. In contrast, in an electrophoretic-mobility-shift assay (EMSA) of crude RAW 264.7 macrophage-like cell extracts, an antiserum that recognizes both AUF1 and CBF-A failed to supershift complexes formed on the TNF-α ARE, but did supershift a complex specific for the COX-2 ARE. CBF-A exists as two isoforms, p37 and p42, that differ by a 47-amino-acid insertion close to the C-terminus. By expressing epitope-tagged isoforms of CBF-A it was shown that the p42 isoform binds the COX-2 ARE in EMSA of crude cell extracts. In a HeLa-cell tetracycline-regulated reporter system, overexpression of the p42 CBF-A isoform resulted in stabilization of a COX-2 ARE reporter mRNA. Epitope-tagged p42 CBF-A expressed in HeLa cells co-immunoprecipitated with endogenous COX-2 mRNA, but not glyceraldehyde-3-phosphate dehydrogenase mRNA, as shown by reverse-transcription PCR. The similarity between CBF-A and AUF1 suggests that CBF-A could be re-named AUF2.